On the Channel and Type of International Disaster Aid - Raschky, Paul A.; Schwindt, Manijeh (2012)
Research suggests that a donor country s decision to provide post-disaster assistance is not only driven by the severity of a disaster and the resulting humanitarian needs in the recipient country, but also by strategic considerations. The authors argue that the identification of the determinants of the size of disaster assistance is a first step in the analysis of the donor s behavior. Since all aid is not motivated by the same reasons, the evaluation of the donor country s behavior requires a second step accounting for the type and the channel of aid provided. Using data on international disaster assistance between 2000 and 2007, the analysis examines both the donor countries' decision on the channel (bilateral versus multilateral) and the type of disaster relief (cash versus in-kind). The empirical results suggest that international disaster relief is not as much driven by the needs of the recipient country, but also by strategic interests (for example, oil or trade relationships) of the donor country. Bilateral and cash transfers are used as a vehicle to signal strategic interests, while multilateral and in-kind transfers are chosen to control for misuse in badly governed recipient countries.